The Influence Of Inquiry-Based Contextual Approach (CTL) On Student Learning Outcomes - Wawan Muliawan; Zuliana Rohmani; Baiq Jauziati (IJE : Interdisciplinary Journal of Education, 2023)
The purpose of this study was to determine the effect of using an inquiry-based contextual approach (CTL) on student learning outcomes in Integrated Science learning (Biology) in class VII students of MTs NW Tebaban in the 2022 academic year. This type of research is a quasi-experimental. The population in this study were students of class VII MTs NW Tebaban. By using the random sampling technique, two classes were obtained as the sample class, the experimental group was class VIIB and the control group was class VIIA. Data collection techniques use learning achievement tests, and student observation sheets. Based on the results of research and discussion that the average value of the experimental class was 79.24 while the control class was 69.5. So it can be concluded that the learning outcomes of the experimental class group are higher than the learning outcomes of the control class group. Meanwhile, based on the results of the normality and homogeneity tests of the two groups, the data were normally distributed and homogeneous, and had relatively the same initial conditions, so a two-party t-test was used to test the hypothesis. From the calculation results, obtained tcount = 4.06 while the value of ttable = 1.68. therefore tcount>ttable, so Ho is rejected and Ha is accepted. So that it can be concluded that there is an influence of Inquiry-Based Contextual Approach (CTL) on Learning Outcomes of Grade VII MTS NW Students in Integrated Science Subjects